The Interplay of Content Marketing and Brand Awareness in Driving TikTok Shop Purchases - Jeaniefer, Jeaniefer; Sutrisno , Julius; Wijaya , Steffie Debbyana; Novytasari , Delvy (Journal of Business, Management, and Social Studies, 2024)
Objective This study aims to analyze the effect of content marketing and brand awareness of TikTok Shop on purchase intention. Methodology This research uses quantitative methods with a quantitative descriptive analysis approach. The type of research is explanatory research which aims to explain the relationship between research variables. The research population is all TikTok Shop users in DKI Jakarta aged 17-30. Samples were taken randomly from the population. Data collection was carried out through an online survey using Google Forms. Findings The findings demonstrated that purchase intention is positively and significantly impacted by content marketing and brand awareness. Given that brand recognition has a higher coefficient value than content marketing, it has to be given greater priority. Novelty The study examines the combined effect of content marketing and brand awareness on purchase intention. This combination of variables provides a more comprehensive understanding of how these factors interact to influence consumer behavior.